Two new species of the cheilostome bryozoan Cheilopora from the Aleutian Islands - Kuklinski, Piotr; Grischenko, Andrei V.; Jewett, Stephen C. (Zootaxa, 2015)
Two new species of Cheilopora—C. peristomata and C. elfa—are described from the shallow water around Adak and Amchitka of the Andreanof and Rat island groups of the Aleutian Islands. Zooids of both new species have cormidial peristomes, composed by the distal (originating from neighbouring zooid) and proximal lappets. In contrast to previously described species, the strongly elevated peristomial lappets defining the secondary orifice confer the overall shape of an incomplete circle with deep U-shaped proximolateral pseudosinuses. Depending on angle of view, this gives a campanuliform or trifoliate outline to the secondary orifice, by which the new species differ from congeners. Together with previous discoveries from the Aleutians, these two new Cheilopora species are indicative of incomplete knowledge of the marine biodiversity of the region, including the distinctive character of the bryozoan fauna. There is a need for intensification of taxonomic effort along the island arc.